THE INVERSE PROBLEM OF FINDING THE RETARDATION FACTOR a2 AND THE DIFFUSION COEFFICIENT D IN A SUBSTANCE TRANSPORT EQUATION IN A HOMOGENEOUS POROUS MEDIUM (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
The equations of solute transport in the one-dimensional case are written in the form